MODULAR TECHNOLOGY OF FOREIGN LANGUAGE TEACHING TO ADULT LEARNERS IN THE SYSTEM OF ADDITIONAL EDUCATION - Evgeniia Ganitskaya; Natalia Moskovskaya (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the fundamentals of developing education programmes based on modular system of foreign language teaching to adults in the system of additional education. The article presents the way of programme creating, describes its structure and its constituent components. It lays great emphasis on adult learners 'peculiarities and the necessity to take them into account while creating programmes.